Influence of the molecular structure on acoustic absorption in the group or saturated ketones - LINDE, B. B.; ŚLIWIŃSKI, A. (Archives of Acoustics, 1994)
The results of acoustic investigation into some heterocyclic liquids showed very close relation between ultrasonic absorption and structure of chemical molecules [1, 2, 3].